PENGARUH PENGGUNAAN MEDIA GOOGLE EARTH TERHADAP KEMAMPUAN GEOSPASIAL SISWA MATA PELAJARAN IPAS KELAS V SDN 12 KOTO BARU - Dhara Atika Putri; Dwi Novri Asmara; Sri Rahmadani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using Google Earth media on the geospatial abilities of fifth-grade students in the IPAS subject at SDN 12 Koto Baru. The background of this research is the low geospatial ability of students due to the lack of interactive technology-based media and the abstract nature of IPAS materials regarding the Earth. This research uses a quantitative approach with a Pre-Experimental Design and a One Group Pretest-Posttest Design. The population and sample consisted of 12 fifth-grade students using saturated sampling. The data collection instrument was a 25-item multiple-choice test that had been tested for validity and reliability. Data analysis was performed using the Shapiro-Wilk normality test and the Paired Sample T-Test with the help of SPSS 27. The results showed that the average pretest score was 41.33 and the posttest score was 63.67. The hypothesis test obtained a Sig. (2-tailed) value of 0.001 < 0.05, meaning H₀ is rejected and Hₐ is accepted. It is concluded that there is a significant effect of using Google Earth media on the geospatial abilities of fifth-grade students at SDN 12 Koto Baru